Quantification of total calcium in terminal cisternae of skinned muscle fibers by imaging electron energy-loss spectroscopy - Stegmann, Heiko; Wepf, Roger; Schröder, Rasmus R.; Fink, Rainer (Journal of muscle research and cell motility, 1999)
Skinned muscle fibers are ideal model preparations for the investigation of Ca2+-regulatory mechanisms. Their internal ionic milieu can be easily controlled and distinct physiological states are well defined. We have measured the total Ca content in the terminal cisternae of such preparations using imaging electron energy-loss spectroscopy (Image-EELS) as a new approach for quantification of sub-cellular element distributions. Murine muscle fibers submitted to a standardized calcium-loading procedure were cryo-fixed with a combined solution exchanger/plunge freezing device. Energy-filtered image series were recorded from ultrathin freeze-dried cryosections of samples immobilized in either relaxed or caffeine-contracted state. From these image series, electron energy-loss spectra were extracted by digital image-processing and quantitatively processed by multiple-least-squares-fitting with reference spectra. The calculated fit coefficients were converted to Ca-concentrations by a calibration obtained from Ca-standards. Total Ca-contents in the terminal cisternae of skinned skeletal muscle fibers decreased upon caffeine-induced Ca-release from 123 ± 159 (±11) to 73 ± 102 (±8) mmol/kg d.w. (weighted mean ± SD (±SEM)).